2012
DOI: 10.1074/jbc.m112.399816
|View full text |Cite
|
Sign up to set email alerts
|

Spider Glue Proteins Have Distinct Architectures Compared with Traditional Spidroin Family Members

Abstract: Background: Spiders extrude adhesive glues to form connection joints that mediate web construction and prey wrapping. Results: DNA microarray analysis and mass spectrometry reveal new protein glue constituents that comprise connection joints. Conclusion: Spider glue proteins represent a diverse group of polypeptides with distinct molecular architectures. Significance: Learning how spider glues mediate the fusion of fibers is crucial for understanding adhesion mechanisms in biology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
56
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(57 citation statements)
references
References 37 publications
(36 reference statements)
1
56
0
Order By: Relevance
“…Cement collections display a matted, nanofibrillar ultrastructure1213495051, that forms in both sealed and porous attachment conditions, and is readily dissolved by polar solvents used to solubilize biomaterials rich in hydrogen bonds and β-sheet structures525354. Relative abundance of proteins in MS/MS data confirms PAGE observations, where Aa43 and polar GSrCPs occupy a significant fraction of cement.…”
Section: Discussionsupporting
confidence: 64%
“…Cement collections display a matted, nanofibrillar ultrastructure1213495051, that forms in both sealed and porous attachment conditions, and is readily dissolved by polar solvents used to solubilize biomaterials rich in hydrogen bonds and β-sheet structures525354. Relative abundance of proteins in MS/MS data confirms PAGE observations, where Aa43 and polar GSrCPs occupy a significant fraction of cement.…”
Section: Discussionsupporting
confidence: 64%
“…It is the glycoprotein composition that primarily determines stickiness in orb web gluey silks (Sahni et al, 2014b). Henceforth the differential expression of aggregate glycoprotein (Choresh et al, 2009;Vasanthavada et al, 2012;Collin et al, 2016) remains a plausible alternative explanation for the differences in spiral stickiness between spiders in the cricket and cockroach feeding treatments. Spread and extension of the glycoproteins under load is, nevertheless, enhanced if the glycoproteins are sufficiently hydrated (Stellwagen et al 2014;Opell et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Biochemical studies demonstrated that the SCP-1 peptide has intrinsic metal binding properties, suggesting a role of peptide-metal ion interactions with the fiber constituents to enhance thread performance [44]. In L. hesperus the aggregate gland has also been shown to produce two different proteins, aggregate gland silk factor 1 (AgSF1) and aggregate gland silk factor 2 (AgSF2) [47]. These proteins were found to be co-localized to the connection joints of both webs and wrapping silks spun from the black widow spider.…”
Section: Spider Silk Types and Their Modulesmentioning
confidence: 99%
“…In case of AgSF2, the consensus novel repetitive sequence, NVNVN, was determined. The amino acid block repeats were found to be embedded in a glycine-rich matrix of AgSF2 [47]. Adhesive spider silk proteins (glues) are important members of the silk family that allow spiders to perform a variety of tasks, such as web construction, prey capture, and locomotion.…”
Section: Spider Silk Types and Their Modulesmentioning
confidence: 99%